KONJUNGSI TEMPORAL DALAM KUMPULAN CERITA RAKYAT MELAYU JAMBI TULISAN ISKANDAR ZAKARIA (ANALISIS WACANA) - Uli Wahyuni; Nurshella Amhar Rasidah (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
This research is aimed at describing the forms and usage of temporal conjunction by using Indriani and Chaer theory. This research explains the forms and usage of temporal conjunction in the kumpulan cerita rakyat Melayu Jambi by Iskandar Zakaria. This research is qualitative descriptive. The data of this research is kumpulan cerita rakyat Melayu Jambi by Iskandar Zakaria (Discourse Analysis). The technique of data collection is by using documentation technique. The result of this research shows the description about the forms and usage of temporal conjunction in the Kumpulan Cerita Rakyat Melayu Jambi by Iskandar Zakaria (Discourse Analysis). Those forms are ketika, sewaktu, sementara, sebelum, setelah, and selagi. Those forms are specified based on the sequence of permulaan, waktu bersamaan, waktu berurutan, and waktu batas akhir in which each of them has their own function.